(untitled) (Journal of Pathology of Nepal, 2017)
Background: Bacterial colonization of central venous catheter (CVC) carries risk of developing catheter-related blood stream infections (CRBSI). The purpose of this study is to find out the frequency of colonization of CVC by different bacterial pathogens and their antibiotic sensitivity pattern. Materials and Methods: A total of 53 CVC tip were received in one-year duration for culture and antibiotic sensitivity pattern. The isolated organisms were identified by standard microbiological procedure and subjected to antimicrobial sensitivity. Results: out of 53 CVC tip sent for culture and sensitivity, 21 (39.6%) showed significant growth. Out of 21 culture positive 52.3% were gram negative bacilli, 33.3% were gram positive cocci, 4.8% were Candida spp. Acenitobacter baumannii and Staphylococcus aureus were frequent pathogens isolated. Gram negative bacteria were less sensitive to antibiotics whereas gram positive bacteria were sensitive to Vancomycin. Conclusion: Though various organisms were isolated as colonizer of CVC, Acenitobacter baumannii is the most common colonizer. Antibiotic resistance has already emerged and represents a major problem.